2014
DOI: 10.1155/2014/235638
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Aluminum Doped Zinc Oxide Nanostructures via Hydrothermal Route

Abstract: Stable crystalline aluminum doped zinc oxide (AZO) nanopowders were synthesized using hydrothermal treatment processing. Three different aluminum precursors have been used. The Al-precursors were found to affect the morphology of the obtained nanopowders. AZO nanoparticles based on zinc acetate and aluminum nitrate have been prepared with different Al/Zn molar ratios. XRD investigations revealed that all the obtained powders have single phase zincite structure with purity of about 99%. The effect of aluminum d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…Thin film properties such as crystal structures, surface structures, band gap and optical absorption and electrical/optical conductivity of ZnO has been improved by introducing dopants in to ZnO lattice [4]. The transition metals (Al, Cu, Ni, Ag, Co) doped ZnO show better properties which are suitable for photovoltaic (PV) application, as these metals have ionic radius nearly similar to ZnO [5,6]. Al 3+ has been the most used dopant element due to its small ionic radius and low material cost.…”
Section: Introductionmentioning
confidence: 99%
“…Thin film properties such as crystal structures, surface structures, band gap and optical absorption and electrical/optical conductivity of ZnO has been improved by introducing dopants in to ZnO lattice [4]. The transition metals (Al, Cu, Ni, Ag, Co) doped ZnO show better properties which are suitable for photovoltaic (PV) application, as these metals have ionic radius nearly similar to ZnO [5,6]. Al 3+ has been the most used dopant element due to its small ionic radius and low material cost.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly the crystallite size decreases moderately with the dopant addition until cobalt concentrations of 0.6% (2 strips of cobalt), where the increment of cobalt content seems to promote the growth of crystallites. As reported for other authors, the decrease tendency in grain size is typically associated to the substitution of Zn +2 by dopant atoms, whose introduce a structure asymmetry that limits the crystallite growth [31,[33][34]62]. Our results suggest that until 0.6% of cobalt addition, the dopant atom occupies the tetrahedral sites of zinc, decreasing the ZnO crystallite until 18nm.…”
Section: Cobalt Influence On the Crystal And Electronic Structure Of Znosupporting
confidence: 80%
“…Since XRD patterns depict the formation of Wurtzite structure indifferently from the cobalt concentration, the increment in mean crystallite size for samples with higher cobalt concentration may indicate the appearance of segregates with bigger crystallite sizes as reported by Alkahlout et al where they have doped zinc oxide with aluminum 34 . In their study, doping…”
Section: Cobalt Influence On the Crystal And Electronic Structure Of Znomentioning
confidence: 74%
See 1 more Smart Citation
“…Aluminium doped ZnO (AZO) has received wider recognition for its high transparency, gassensing property, stability, good conductivity and optical properties. Mondal et al [4], Tarasov and Raccurt [5], Alkahlout et al [6], and many other scientists reported blue shift in AZO nanomaterials, identified to be the Burstein-Moss effect. Doping of ZnO with Al was also attempted by other researchers to realize transparent ohmic contact for applications such as n-type layers in photovoltaic devices, especially in solar cells, FET and lightemitting devices [7].…”
Section: Introductionmentioning
confidence: 97%